Eutectic high-entropy alloy / copper layered composite material with graphene-reinforced bionic configuration and preparation method of eutectic high-entropy alloy / copper layered composite material
Preparation of graphene-enhanced eutectic high-entropy alloy/copper layered composite materials by selective laser melting and vacuum hot pressing methods, solving the problem of difficulty in balancing the strength and ductility of single-phase high-entropy alloys, significantly improving the pressure resistance Performance and fracture strain performance ensure high-quality interface combination.
Patent Information
- Application Number
- CN202411032831.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2024-12-13
AI Technical Summary
Single-phase high-entropy alloys are difficult to achieve a balance between high strength and high ductility, and it is difficult to prepare eutectic high-entropy alloy/copper layered composite materials with excellent mechanical properties in the prior art.
The bionic configuration pore-like eutectic high-entropy alloy framework was prepared by selective laser melting equipment, and the copper graphene powder was filled into the holes by vacuum hot pressing to form a graphene-enhancing eutectic high-entropy alloy/copper layer. shaped composite material.
The compressive resistance and fracture strain properties of the composite material are improved, and the interface bonding quality is smooth, without obvious cracks and hole defects, achieving high strength and good plasticity.
Smart Images

Figure CN119114965A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of eutectic high entropy alloys, and in particular to a graphene-enhanced bionic eutectic high entropy alloy / copper layered composite material and a preparation method thereof. Background Art
[0002] High entropy alloy (HEAs) is a multi-component alloy containing four or more main elements in equiatomic or near-equiatomic ratios. In recent years, it has attracted increasing attention due to its unique atomic structure and properties.
[0003] Recent studies have shown that single-phase face-centered cubic (FCC) phase HEAs and body-centered cubic (BCC) phase HEAs have been widely studied, but single-phase FCC HEAs usually have high ductility but low yield strength, while single-phase BCC HEAs have high yield strength but low ductility. It is difficult for single-phase HEAs to achieve a balance between high strength and high ductility. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a graphene-enhanced bionic eutectic high entropy alloy / copper layered composite material and a preparation method thereof, which has a simple process and is easy to implement.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for preparing a graphene-enhanced bionic eutectic high-entropy alloy / copper layered composite material comprises the following steps:
[0007] S1. A eutectic high entropy alloy skeleton structure diagram of a bionic porous eutectic high entropy alloy skeleton structure is obtained by computer software design. The bionic porous eutectic high entropy alloy skeleton structure includes an alloy skeleton and pores densely distributed in the alloy skeleton;
[0008] The selective laser melting equipment receives the eutectic high entropy synthesis skeleton structure diagram, and before starting the selective laser melting equipment, the eutectic high entropy synthesis skeleton structure diagram is firstly sliced by the processing software of the selective laser melting equipment, the molding substrate is mounted on the molding platform of the selective laser melting equipment and leveled, the equipment cavity of the selective laser melting equipment is sealed, and then high-purity argon gas is introduced for protection;
[0009] S2, the dried AlCoCrFeNi 2.1 Eutectic high entropy alloy powder is sent to the powder feeding cylinder inside the selective laser melting equipment. The selective laser melting equipment uses AlCoCrFeNi 2.1 Eutectic high entropy alloy powder is melted layer by layer and formed on a forming substrate. AlCoCrFeNi2.1 Transformation of eutectic high entropy alloy powder into dual-phase AlCoCrFeNi 2.1 Eutectic high entropy alloy, preparation of biomimetic porous AlCoCrFeNi with dual-phase lamellar nanostructure 2.1 Eutectic high entropy alloy skeleton;
[0010] S3, the bionic configuration porous AlCoCrFeNi obtained in step S2 2.1 The surface of the eutectic high entropy alloy skeleton is finely ground and polished, and after ultrasonic cleaning and drying, it is placed in a graphite mold in a vacuum hot press furnace. 2.1 The copper graphene powder is filled above and below the eutectic high entropy alloy skeleton, and the copper graphene powder forms a bionic porous AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton is completely wrapped;
[0011] S4, transferring the graphite mold into the furnace chamber of a vacuum hot pressing furnace, evacuating the furnace chamber of the vacuum hot pressing furnace and then introducing argon protective gas for vacuum hot pressing sintering, the copper graphene powder in each hole is converted into copper graphene structure by hot pressing and fills the hole, and the interface between the hole and the copper graphene structure is smooth and has no gaps, wherein,
[0012] The copper-graphene powder and the porous AlCoCrFeNi2.1 eutectic high-entropy alloy skeleton with a bionic configuration in a graphite mold are sequentially subjected to cold pressing into a blank, heating treatment at a high temperature, heat preservation and pressurization treatment, and pressure holding treatment. After pressure holding, they are cooled in the furnace to obtain a eutectic high-entropy alloy / copper layered composite material with a graphene-enhanced bionic configuration.
[0013] According to a further technical solution, the copper-graphene powder is a mixed powder formed by mixing pure copper powder and graphene powder, and the mass ratio content of graphene in the copper-graphene powder is 0-1wt%.
[0014] According to a further technical solution, the copper-graphene powder is a mixed powder formed by mixing pure copper powder and graphene powder, and the mass ratio content of graphene in the copper-graphene powder is 0.2-0.5wt%.
[0015] In a further technical solution, in step S2, the eutectic high entropy alloy powder used is AlCoCrFeNi 2.1 Alloy powder, AlCoCrFeNi 2.1 The particle size of alloy powder is 15-53μm, AlCoCrFeNi 2.1 The fluidity of the alloy powder is 16-20s / 50g.
[0016] In a further technical solution, in step S3, the copper graphene powder prepared by vacuum hot pressing of the composite material is obtained by atomization powder making, has good powder fluidity, uniform powder particle size distribution and powder particle size close to AlCoCrFeNi 2.1 The average particle size of the alloy powder, the powder particle size of 15-53 μm, the powder and the bionic configuration porous AlCoCrFeNi 2.1 The order of placing the eutectic high entropy alloy skeleton from top to bottom is 6 mm thick powder, bionic porous AlCoCrFeNi 2.1 Eutectic high entropy alloy skeleton, powder with a thickness of 6 mm.
[0017] Further technical solution, in step S1, the selective laser melting scanning strategy and process parameters are set by the selective laser melting equipment, and the set selective laser melting process parameters include: scanning path is 65-70° layer-by-layer scanning, spot diameter is 60-80μm, laser energy density is 80-170J / mm 3 , laser power is 150-350W, scanning speed is 650-850mm / s, single-channel scanning spacing is 0.08-0.1mm, and powder layer thickness is 0.03-0.05mm.
[0018] In a further technical solution, in step S2, the AlCoCrFeNi 2.1 The drying treatment of the eutectic high entropy alloy powder is carried out by keeping the temperature at 150-180°C for 1-3 hours.
[0019] According to a further technical solution, in step S2, the molding substrate is a 304 stainless steel molding substrate, which is first preheated at 200-250° C. for 0.5-2 hours before being installed on the molding platform.
[0020] A further technical solution is that in the step S3, the pressure of the cold pressing process is 15 MPa, the heating rate of the heating process is 10°C / min, the heating rate is controlled slowly to ensure that the powder is heated evenly, the temperature is raised to 900°C and then kept warm, and the pressure is raised to 50 MPa and kept warm for 1 hour during the heat preservation and pressure treatment process; in the step S4, the vacuum treatment is performed to make the vacuum degree of the furnace chamber reach 1×10 -2 Pa, maintaining a high vacuum state to prevent the powder from being oxidized after being heated at high temperature during the test.
[0021] A further technical solution is that the bionic configuration porous AlCoCrFeNi 2.1The eutectic high entropy alloy skeleton comprises a plurality of thin main walls and a plurality of thin connecting walls, wherein the main walls are parallel to each other and are arranged at intervals, and a plurality of connecting walls are integrally connected between two adjacent main walls, and the two adjacent main walls and the two adjacent connecting walls shield to form a longitudinally extending hole, and each hole longitudinally penetrates the bionic structure pore-shaped AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton has pores filled with copper-graphene structures formed by vacuum hot-pressing and sintering the copper-graphene powder.
[0022] A graphene-enhanced bionic eutectic high entropy alloy / copper layered composite material, comprising the above-mentioned bionic porous AlCoCrFeNi having a plurality of pores densely distributed therein 2.1 Eutectic high entropy alloy skeleton and copper graphene structure filled with each of the holes, biomimetic configuration porous AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton has a plurality of thin main walls and a plurality of thin connecting walls, each main wall is parallel to each other and arranged at intervals, a plurality of connecting walls parallel to each other and arranged at intervals are integrally connected between two adjacent main walls, and the two adjacent main walls and the two adjacent connecting walls shield to form a longitudinally extending hole, and each hole longitudinally penetrates the bionic structure pore-shaped AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton has pores filled with copper-graphene tissue formed by vacuum hot-pressing and sintering the copper-graphene powder, and the interface between the pores and the copper-graphene tissue is smooth and void-free.
[0023] Compared with the prior art, the present invention has the following advantages: the present invention uses a selective laser melting device to prepare a bionic porous AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton is combined with a vacuum hot pressing method to prepare a eutectic high entropy alloy / copper layered composite material with a graphene enhanced bionic configuration. The process is simple and easy to implement. The interface bonding quality of the overall eutectic high entropy alloy / copper-based graphene composite material is good, the composite interface is flat and smooth, without obvious cracks and hole defects, and the compressive resistance and fracture strain properties are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is the structural diagram of the selective laser melting equipment and the forming sample diagram;
[0025] Figure 2 For selective laser melting of AlCoCrFeNi 2.1 Photo of eutectic high entropy alloy skeleton microstructure;
[0026] Figure 3 Schematic diagram of preparing eutectic high entropy alloy / copper composite material by vacuum hot pressing;
[0027] Figure 4 This is a microstructure photo of eutectic high entropy alloy / copper composite material prepared by vacuum hot pressing;
[0028] Figure 5 Raman spectrum of graphene in eutectic high entropy alloy / copper graphene composite prepared by vacuum hot pressing; Figure 6 The experimental results of compression properties of eutectic high entropy alloy / copper and eutectic high entropy alloy / copper graphene composites prepared by vacuum hot pressing. DETAILED DESCRIPTION
[0029] Example 1
[0030] A method for preparing a graphene-enhanced bionic eutectic high-entropy alloy / copper layered composite material comprises the following steps:
[0031] (1) Processing of pre-alloyed powders,
[0032] The screening of AlCoCrFeNi 2.1 Eutectic high entropy alloy powder, AlCoCrFeNi with a particle size of 15-53μm 2.1 Eutectic high entropy alloy powder, then AlCoCrFeNi 2.1 The eutectic high entropy alloy powder was placed in a drying oven for drying, heated to 150°C in a vacuum environment, and then dried for 3 hours, and then cooled in the oven. 2.1 Eutectic high entropy alloy powder is added into the powder feeding cylinder of the selective laser melting equipment.
[0033] (2) Pretreatment of molding substrate materials,
[0034] The molding substrate material is a 304 stainless steel molding substrate. The upper surface of the 304 stainless steel molding substrate is sandblasted in advance with a sandblasting machine, then cleaned with acetone to remove surface debris, and then cleaned and dried with alcohol. Finally, the 304 stainless steel molding substrate is installed on the molding platform and leveled, and preheated at 200°C for 0.5-2 hours before molding.
[0035] (3) Preparation of biomimetic porous eutectic high entropy alloy skeleton by selective laser melting.
[0036] First, the selective laser melting equipment was turned on and the scanning path was set. The process parameters included laser power 350W, scanning speed 850mm / s, single-pass scanning spacing 0.1mm, and powder layer thickness 0.03mm. Under the protection of high-purity argon, the eutectic high-entropy alloy skeleton sample was prepared by selective laser melting in a closed chamber. Figure 1 shown.
[0037] (4) Selected laser melting sample test,
[0038] The present invention adopts selective laser melting AlCoCrFeNi 2.1 The skeleton microstructure of eutectic high entropy alloy is as follows Figure 2 As shown in the figure, compared with the cast structure, the eutectic high entropy alloy prepared by the selective laser melting technology in the present invention has a uniform and fine microstructure, and its mechanical properties are higher than those of the bionic porous AlCoCrFeNi prepared by casting. 2.1 Eutectic high entropy alloy skeleton. The reason is that the selective laser melting technology has a faster cooling rate, fine microstructure and high density.
[0039] (5) Biomimetic porous AlCoCrFeNi 2.1 Pretreatment of eutectic high entropy alloy skeleton,
[0040] The prepared biomimetic porous AlCoCrFeNi 2.1 The upper and lower surfaces of the eutectic high entropy alloy skeleton were finely polished, cleaned with alcohol ultrasonic and blown dry, and then stored in a vacuum for later use. Figure 3 As shown in the figure, copper powder with a particle size of 15-53 μm is placed at the bottom of a circular graphite mold in a hot pressing furnace with a filling height of 6 mm, and then the bionic porous AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton is placed on the copper powder and then pre-compacted with a graphite mold to form a bionic porous AlCoCrFeNi 2.1 Copper powder is stacked on the eutectic high entropy alloy skeleton, and the bionic porous AlCoCrFeNi 2.1 The copper powder on top of the eutectic high entropy alloy skeleton has a stacking height of 6 mm, which is compacted with a graphite mold cylindrical core and then placed in a vacuum hot pressing device.
[0041] (6) Preparation of graphene-enhanced biomimetic eutectic high entropy alloy / copper layered composites by vacuum hot pressing.
[0042] After adjusting the graphite mold to align with the center position of the hydraulic cylinder in the hot pressing system, start the vacuum system of the hot pressing equipment and evacuate to 1×10 -2 Pa, and then argon protective gas is introduced. First, the powder loaded in the mold is cold pressed in a vacuum environment, and a pressure of 15MPa is applied and maintained for 10 minutes; then, it is heated to 900℃ at a heating rate of 10℃ / min, and the pressure program is started after 30 minutes of heat preservation, and the pressure increase program is completed within 10 minutes, the pressure is increased to 50MPa and the pressure is maintained for 1 hour. Finally, the heating system and pressure system are turned off, and the furnace is cooled to room temperature, and the sample is taken out for testing.
[0043] (7) Test and characterization of graphene-enhanced bionic eutectic high entropy alloy / copper layered composite materials,
[0044] Some samples were taken for testing by electrospark machining. Figure 4 a is the microstructure of the eutectic high entropy alloy / copper composite material (Cu / EHEA) observed by scanning electron microscopy. There are no obvious cracks and holes at the composite interface. After the interface is magnified, it is found that no brittle intermetallic compounds are generated at the interface. The elements in the high entropy alloy and the copper side diffuse significantly, and a eutectic high entropy alloy / copper composite sample with good interface quality can be obtained, indicating the feasibility of the vacuum hot pressing method to prepare eutectic high entropy alloy / copper composite materials. Figure 4 a1. Then the compression performance test of Cu / EHEA composite material was carried out, and the test results are shown in Figure 6 As shown, the compressive strength of the eutectic high entropy alloy / copper layered composite material is 661.9 MPa, and its fracture strain reaches 30.2%, indicating that the composite material has high compressive strength and good plasticity.
[0045] Example 2
[0046] A method for preparing a graphene-enhanced bionic eutectic high-entropy alloy / copper layered composite material comprises the following steps:
[0047] (1) Processing of pre-alloyed powders,
[0048] The screening of AlCoCrFeNi 2.1 Eutectic high entropy alloy powder, AlCoCrFeNi with a particle size of 15-53μm 2.1 Eutectic high entropy alloy powder, then AlCoCrFeNi 2.1 The eutectic high entropy alloy powder was placed in a drying oven for drying, heated to 150°C in a vacuum environment, and then dried for 3 hours, and then cooled in the oven. 2.1 Eutectic high entropy alloy powder is added into the powder feeding cylinder of the selective laser melting equipment.
[0049] (2) Pretreatment of molding substrate materials,
[0050] The molding substrate material is a 304 stainless steel molding substrate. The upper surface of the 304 stainless steel molding substrate is sandblasted in advance with a sandblasting machine, then cleaned with acetone to remove surface debris, and then cleaned and dried with alcohol. Finally, the 304 stainless steel molding substrate is installed on the molding platform and leveled, and preheated at 200°C for 0.5-2 hours before molding.
[0051] (3) Preparation of biomimetic porous eutectic high entropy alloy skeleton by selective laser melting.
[0052] First, the selective laser melting equipment was turned on and the scanning path was set. The process parameters included laser power 350W, scanning speed 850mm / s, single-pass scanning spacing 0.1mm, and powder layer thickness 0.03mm. Under the protection of high-purity argon, the eutectic high-entropy alloy skeleton sample was prepared by selective laser melting in a closed chamber. Figure 1 shown.
[0053] (4) Selected laser melting sample test,
[0054] The present invention adopts selective laser melting AlCoCrFeNi 2.1 The skeleton microstructure of eutectic high entropy alloy is as follows Figure 2 As shown in the figure, compared with the cast structure, the eutectic high entropy alloy prepared by the selective laser melting technology in the present invention has a uniform and fine microstructure, and its mechanical properties are higher than those of the bionic porous AlCoCrFeNi prepared by casting. 2.1 Eutectic high entropy alloy skeleton. The reason is that the selective laser melting technology has a faster cooling rate, fine microstructure and high density.
[0055] Biomimetic porous AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton comprises a plurality of thin main walls and a plurality of thin connecting walls, wherein the main walls are parallel to each other and are arranged at intervals, and a plurality of connecting walls are integrally connected between two adjacent main walls, and the two adjacent main walls and the two adjacent connecting walls shield to form a longitudinally extending hole, and each hole longitudinally penetrates the bionic structure pore-shaped AlCoCrFeNi 2.1 Eutectic high entropy alloy skeleton.
[0056] (5) Biomimetic porous AlCoCrFeNi 2.1 Pretreatment of eutectic high entropy alloy skeleton,
[0057] The prepared bionic porous AlCoCrFeNi 2.1 The upper and lower surfaces of the eutectic high entropy alloy skeleton were finely ground and polished, cleaned and dried by alcohol ultrasonic cleaning, and stored in a vacuum for later use.
[0058] The copper-based graphene powder is placed in the hot press furnace and filled with 6mm high at the bottom of the circular graphite mold. The eutectic high entropy alloy skeleton is placed on the copper powder and pre-compacted with a graphite mold. Then the copper-based graphene powder is added to fill the total height to about 18mm, compacted with a cylindrical core of the graphite mold, and placed in a vacuum hot press. Powder and biomimetic configuration of porous AlCoCrFeNi 2.1 The order of placing the eutectic high entropy alloy skeleton from top to bottom is 6 mm thick powder, bionic porous AlCoCrFeNi 2.1 Eutectic high entropy alloy skeleton, powder with a thickness of 6 mm.
[0059] Among them, copper graphene powders are all obtained by atomization powder making, with good powder fluidity, uniform powder particle size distribution and powder particle size close to AlCoCrFeNi 2.1 The average particle size of the alloy powder is 15-53 μm, the copper-graphene powder is a mixed powder of pure copper powder or graphene powder, and the mass ratio content of graphene in the copper-graphene powder is 0.2-0.5wt%. The mass ratio content of graphene in the copper-graphene powder used in this embodiment 2 is 0.3wt%.
[0060] (6) Preparation of graphene-enhanced biomimetic eutectic high entropy alloy / copper layered composites by vacuum hot pressing.
[0061] After adjusting the graphite mold to align with the center position of the hydraulic cylinder in the hot pressing system, start the vacuum system of the hot pressing equipment and draw the vacuum to 1×10 -2 Pa, and argon protective gas is introduced. First, the powder loaded in the mold is cold pressed in a vacuum environment, and a pressure of 15MPa is applied and maintained for 10 minutes. Then, it is heated to 900℃ at a heating rate of 10℃ / min. After being kept warm for 30 minutes, the pressure program is started and the pressure is increased to 50MPa within 10 minutes and the pressure is maintained for 1 hour. Finally, the heating system and pressure system are turned off, and the sample is taken out after cooling to room temperature with the furnace.
[0062] Biomimetic porous AlCoCrFeNi 2.1 The pores of the eutectic high entropy alloy skeleton are filled with copper-graphene structures formed by vacuum hot-pressing and sintering the copper-graphene powder. The copper-graphene powder in each pore is transformed into the copper-graphene structure by hot-pressing and fills the pores. The interface between the pores and the copper-graphene structure is smooth and free of gaps.
[0063] (7) Test and characterization of graphene-enhanced bionic eutectic high entropy alloy / copper layered composite materials,
[0064] Some samples were taken for testing by electrospark machining. Figure 4 b is the microstructure of the eutectic high entropy alloy / copper-based graphene (Cu / Gr / EHEA) composite material observed by scanning electron microscopy. The composite interface is flat and smooth without obvious cracks and holes. The magnified observation area is as follows: Figure 4 As shown in b1, the overall eutectic high entropy alloy / copper-based graphene composite material sample has good interface bonding quality, and a eutectic high entropy alloy (EHEA) and copper-based graphene (Cu / Gr) powder layered composite sample with high-quality bonding interface is obtained. Eutectic high entropy alloy / copper-based graphene composite material after vacuum hot pressing Figure 4 The Raman spectrum of the carbon dot region (white circle) in b1 is shown in Figure 5As shown, it shows the typical graphene characteristic peak at 1350cm -1 The D peak originates from the destruction of the original static state of carbon atoms, reflecting the degree of defects in graphene; it is located at 1579-1588cm -1 The G peak originates from the sp 2 Stretching vibration of hybrid atoms, related to the symmetry and crystallinity of graphene; located at 2688-2699 cm -1 The 2D peak originates from the sp 2 The intensity ratio of the 2D peak and the G peak indicates that the number of graphene layers in the eutectic high entropy alloy / copper-based graphene layered composite material is multilayer, indicating that the vacuum hot pressing method can ensure the presence of graphene to prepare the eutectic high entropy alloy / copper-based graphene layered composite material.
[0065] (8) Microstructure characterization of eutectic high entropy alloy / copper layered composites with graphene-enhanced bionic configuration,
[0066] The results of the compression test of the composite material are as follows: Figure 6 As shown, the compressive strength of the eutectic high entropy alloy / copper-based graphene composite material reaches 746.1MPa, and its fracture strain reaches 33.6%. Compared with the compressive strength of the eutectic high entropy alloy / copper composite material in Experimental Case 1, it is increased by 12.7%, and the fracture toughness of the composite material is also slightly improved, indicating that the graphene in the invention has a more obvious reinforcing effect on the eutectic high entropy alloy / copper layered composite material with a bionic configuration, and the invention provides a feasible preparation method for the eutectic high entropy alloy / copper-based graphene layered composite material with a bionic configuration in the field of engineering applications.
[0067] Example 3
[0068] A graphene-enhanced bionic eutectic high entropy alloy / copper layered composite material, prepared according to Example 1 or 2, comprising the bionic porous AlCoCrFeNi having a plurality of holes densely distributed therein 2.1 Eutectic high entropy alloy skeleton and copper graphene structure filled with each of the holes, biomimetic configuration porous AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton has a plurality of thin main walls and a plurality of thin connecting walls, each main wall is parallel to each other and arranged at intervals, a plurality of connecting walls parallel to each other and arranged at intervals are integrally connected between two adjacent main walls, and the two adjacent main walls and the two adjacent connecting walls shield to form a longitudinally extending hole, and each hole longitudinally penetrates the bionic structure pore-shaped AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton has pores filled with copper-graphene tissue formed by vacuum hot-pressing and sintering the copper-graphene powder, and the interface between the pores and the copper-graphene tissue is smooth and void-free.
[0069] Comparative Example 1
[0070] According to steps 1-4 of Example 1, a eutectic high entropy alloy skeleton of the sample of Comparative Example 1 was prepared, and the compressive properties and fracture strain properties thereof were tested, as shown in Table 1.
[0071] Comparative Example 2
[0072] The copper powder in steps 5 and 6 of Example 1 was replaced with aluminum powder, and the sample of Comparative Example 2 was prepared according to the steps of Example 1. The compressive properties and fracture strain properties of the sample were tested, as shown in Table 1.
[0073]
[0074]
[0075] Table 1-Material performance test table
[0076] Eutectic high entropy alloy (EHEA) can have both high strength and high ductility. AlCoCrFeNi 2.1 Eutectic high entropy alloys have a layered structure composed of FCC and BCC, and have an excellent combination of ultimate tensile strength and ductility. The relatively low melting point and narrow eutectic solidification interval of the eutectic structure are conducive to the reduction of alloy defects and easy forming.
[0077] Copper has excellent electrical and thermal conductivity and corrosion resistance, eutectic high entropy alloys have high strength, high hardness and good plasticity and toughness, and the composite structure of dissimilar materials can fully utilize the excellent properties of the two metals or their combination while meeting economic requirements, and has a broad development background in the fields of aerospace, automobiles, electronics and medicine.
[0078] The present invention is inspired by the biological structure of nature, and the multifunctional structural design of metal materials has become a hot topic in the current research field of metal composite materials. Bionic configuration design composite materials can break through the application limitations of traditional single structural materials, achieve the performance of the parent material itself, and give full play to the comprehensive performance advantages of heterogeneous structure composite materials. While having high strength and hardness, they can also have good plasticity and good processing performance. Nowadays, many studies have shown that the current research on eutectic high entropy alloys still remains in the microstructure and performance aspects, and there are few studies on structural design. The change of thermal expansion coefficient of eutectic high entropy alloys with temperature is similar to that of metals without phase change. Eutectic high entropy alloys are used as reinforcements and composited with metal-based composites to overcome some shortcomings of traditional reinforcements. In order to save costs while meeting various performance requirements, research on heterogeneous metal composite materials is particularly important.
[0079] Selective laser melting technology is a highly intelligent new manufacturing technology based on the principle of layered manufacturing. It uses high-energy laser as the heat source and metal powder as the raw material. It accumulates and forms layer by layer on the substrate. It can directly manufacture digital models into physical parts. This preparation method has the advantages of high utilization rate, fast heating and cooling speed, and can form uniform and dense microstructure, uniform distribution of elements in the alloy, fewer microscopic defects, and short process flow. The present invention uses the selective laser melting method to provide a new method for the preparation of eutectic high entropy alloy bionic structure design with complex shape, dense structure, uniform and fine microstructure and excellent performance.
[0080] Graphene has excellent intrinsic functional properties such as thermal conductivity and corrosion resistance. It is an ideal reinforcement for the multifunctionalization of metal-based composite materials. The introduction of graphene into the copper matrix can reduce the thermal expansion coefficient of the copper matrix perpendicular to the in-plane direction, so that the thermophysical properties of the composite material show strong anisotropy, and have a high enhancement effect on the mechanical properties of the composite material. At the same time, combined with the strengthening and toughening effect given by the bionic brick-mud composite configuration, a graphene-enhanced bionic eutectic high-entropy alloy composite with coordinated strength, hardness and plastic toughness is finally prepared. The present invention uses the pearl-like brick-mud configuration inspired by nature as a design template to explore the preparation method of high-strength and tough layered composite materials, and adopts a selective laser melting method combined with a vacuum hot pressing composite process to realize the preparation of a bionic eutectic high-entropy alloy skeleton and the preparation and efficient connection of high-performance heterogeneous metal composites, which is expected to provide a theoretical design basis and data support for complex structural parts in the fields of aerospace, automobiles, and medical treatment.
[0081] The above contents are only preferred embodiments of the present invention. For ordinary technicians in this field, according to the concept of the present invention, there will be changes in the specific implementation methods and application scopes. The content of this specification should not be understood as limiting the present invention.
Claims
1. A method for preparing a graphene-enhanced bionic eutectic high entropy alloy / copper layered composite material, characterized in that: The following steps are included: S1. A eutectic high entropy alloy skeleton structure diagram of a bionic porous eutectic high entropy alloy skeleton structure is obtained by computer software design. The bionic porous eutectic high entropy alloy skeleton structure includes an alloy skeleton and pores densely distributed in the alloy skeleton; The selective laser melting equipment receives the eutectic high entropy synthesis skeleton structure diagram, and before starting the selective laser melting equipment, the eutectic high entropy synthesis skeleton structure diagram is firstly sliced by the processing software of the selective laser melting equipment, the molding substrate is mounted on the molding platform of the selective laser melting equipment and leveled, the equipment cavity of the selective laser melting equipment is sealed, and then high-purity argon gas is introduced for protection; S2, the dried AlCoCrFeNi 2.1 Eutectic high entropy alloy powder is sent to the powder feeding cylinder inside the selective laser melting equipment. The selective laser melting equipment uses AlCoCrFeNi 2.1 Eutectic high entropy alloy powder is melted layer by layer and formed on a forming substrate. AlCoCrFeNi 2.1 Transformation of eutectic high entropy alloy powder into dual-phase AlCoCrFeNi 2.1 Eutectic high entropy alloy, preparation of biomimetic porous AlCoCrFeNi with dual-phase lamellar nanostructure 2.1 Eutectic high entropy alloy skeleton; S3, the bionic configuration porous AlCoCrFeNi obtained in step S2 2.1 The surface of the eutectic high entropy alloy skeleton is finely ground and polished, and after ultrasonic cleaning and drying, it is placed in a graphite mold in a vacuum hot press furnace. 2.1 The copper graphene powder is filled above and below the eutectic high entropy alloy skeleton, and the copper graphene powder forms a bionic porous AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton is completely wrapped; S4, transferring the graphite mold into the furnace chamber of a vacuum hot pressing furnace, evacuating the furnace chamber of the vacuum hot pressing furnace and then introducing argon protective gas for vacuum hot pressing sintering, the copper graphene powder in each hole is converted into copper graphene structure by hot pressing and fills the hole, and the interface between the hole and the copper graphene structure is smooth and has no gaps, wherein, Copper graphene powder in graphite mold and biomimetic porous AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton is subjected to cold pressing into a blank, heating treatment, heat preservation and pressure treatment and pressure holding treatment in sequence, and after pressure holding, it is cooled in a furnace to obtain a eutectic high entropy alloy / copper layered composite material with a graphene enhanced bionic configuration.
2. The method for preparing a graphene-enhanced bionic eutectic high entropy alloy / copper layered composite material according to claim 1, characterized in that: The copper-graphene powder is a mixed powder formed by mixing pure copper powder and graphene powder, and the mass ratio content of graphene in the copper-graphene powder is 0-1wt%.
3. The method for preparing a graphene-enhanced bionic eutectic high-entropy alloy / copper layered composite material according to claim 1, characterized in that: The copper-graphene powder is a mixed powder formed by mixing pure copper powder and graphene powder. The mass ratio content of graphene in the copper-graphene powder is 0.2-0.5wt%.
4. The method for preparing a graphene-enhanced bionic eutectic high-entropy alloy / copper layered composite material according to claim 1, characterized in that: In step S2, the eutectic high entropy alloy powder used is AlCoCrFeNi 2.1 Alloy powder, AlCoCrFeNi 2.1 The particle size of alloy powder is 15-53μm, AlCoCrFeNi 2.1 The fluidity of the alloy powder is 16-20s / 50g.
5. The method for preparing a graphene-enhanced bionic eutectic high-entropy alloy / copper layered composite material according to claim 1, characterized in that: In step S3, the copper graphene powder prepared by vacuum hot pressing of the composite material is obtained by atomization powder making, has good powder fluidity, uniform powder particle size distribution and powder particle size close to AlCoCrFeNi 2.1 The average particle size of the alloy powder, the powder particle size of 15-53 μm, the powder and the bionic configuration porous AlCoCrFeNi 2.1 The order of placing the eutectic high entropy alloy skeleton from top to bottom is 6 mm thick powder, bionic porous AlCoCrFeNi 2.1 Eutectic high entropy alloy skeleton, powder with a thickness of 6 mm.
6. The method for preparing a graphene-enhanced bionic eutectic high-entropy alloy / copper layered composite material according to claim 1, characterized in that: In step S1, the selective laser melting scanning strategy and process parameters are set by the selective laser melting equipment. The set selective laser melting process parameters include: scanning path is 65-70° layer-by-layer scanning, spot diameter is 60-80 μm, laser energy density is 80-170 J / mm 3 , laser power is 150-350W, scanning speed is 650-850mm / s, single-channel scanning spacing is 0.08-0.1mm, and powder layer thickness is 0.03-0.05mm.
7. The method for preparing a graphene-enhanced bionic eutectic high entropy alloy / copper layered composite material according to claim 1, characterized in that: In step S2, the molding substrate is a 304 stainless steel molding substrate, which is first preheated at 200-250° C. for 0.5-2 hours before being installed on the molding platform; the AlCoCrFeNi 2.1 The drying treatment of the eutectic high entropy alloy powder is carried out by keeping the temperature at 150-180°C for 1-3 hours.
8. The method for preparing a graphene-enhanced bionic eutectic high-entropy alloy / copper layered composite material according to claim 1, characterized in that: In the step S3, the pressure of the cold pressing process is 15 MPa, the heating rate of the heating process is 10°C / min, the heating rate is controlled slowly to ensure that the powder is heated evenly, the temperature is raised to 900°C and then kept warm, and the pressure is raised to 50 MPa and kept warm for 1 hour during the heat preservation and pressure treatment process; in the step S4, the vacuum treatment is performed to make the vacuum degree of the furnace chamber reach 1×10 -2 Pa, maintaining a high vacuum state to prevent the powder from being oxidized after being heated at high temperature during the test.
9. The method for preparing a graphene-enhanced bionic eutectic high entropy alloy / copper layered composite material according to claim 1, characterized in that: The bionic configuration of porous AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton comprises a plurality of thin main walls and a plurality of thin connecting walls, wherein the main walls are parallel to each other and are arranged at intervals, and a plurality of connecting walls are integrally connected between two adjacent main walls, and the two adjacent main walls and the two adjacent connecting walls shield to form a longitudinally extending hole, and each hole longitudinally penetrates the bionic structure pore-shaped AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton has pores filled with copper-graphene structures formed by vacuum hot-pressing and sintering the copper-graphene powder.
10. A graphene-enhanced bionic eutectic high entropy alloy / copper layered composite material, characterized in that: The biomimetic porous AlCoCrFeNi having a plurality of pores densely distributed therein as claimed in any one of claims 1 to 9 2.1 Eutectic high entropy alloy skeleton and copper graphene structure filled with each of the holes, biomimetic configuration porous AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton has a plurality of thin main walls and a plurality of thin connecting walls, each main wall is parallel to each other and arranged at intervals, a plurality of connecting walls parallel to each other and arranged at intervals are integrally connected between two adjacent main walls, and the two adjacent main walls and the two adjacent connecting walls shield to form a longitudinally extending hole, and each hole longitudinally penetrates the bionic structure pore-shaped AlCoCrFeNi 2.1 The eutectic high entropy alloy skeleton has pores filled with copper-graphene tissue formed by vacuum hot-pressing and sintering the copper-graphene powder, and the interface between the pores and the copper-graphene tissue is smooth and void-free.
Citation Information
Cited By
Multi-layer bionic structure high-entropy alloy composite material and preparation method thereof
CN122300012A
